2016
DOI: 10.1080/10410236.2016.1214214
|View full text |Cite
|
Sign up to set email alerts
|

Social Representation of Cyberbullying and Adolescent Suicide: A Mixed-Method Analysis of News Stories

Abstract: Cyberbullying has provoked public concern after well-publicized suicides of adolescents. This mixed-methods study investigates the social representation of these suicides. A content analysis of 184 U.S. newspaper articles on death by suicide associated with cyberbullying or aggression found that few articles adhered to guidelines suggested by the World Health Organization and the American Foundation for Suicide Prevention to protect against suicidal behavioral contagion. Few articles made reference to suicide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(31 citation statements)
references
References 47 publications
2
24
0
5
Order By: Relevance
“…Cyberbullying victimization has also been linked to suicide ideation (Mitchell et al, 2018;Nixon, 2014;Young, Subramanian, Miles, Hinnant, & Andsager, 2016). Suicide ideation occurs when an individual repeatedly thinks about, plans, and desires to commit suicide (Beck, Kovacs, & Weissman, 1979).…”
Section: Cyberbullying and Psychosocial Maladjustmentmentioning
confidence: 99%
“…Cyberbullying victimization has also been linked to suicide ideation (Mitchell et al, 2018;Nixon, 2014;Young, Subramanian, Miles, Hinnant, & Andsager, 2016). Suicide ideation occurs when an individual repeatedly thinks about, plans, and desires to commit suicide (Beck, Kovacs, & Weissman, 1979).…”
Section: Cyberbullying and Psychosocial Maladjustmentmentioning
confidence: 99%
“…Suicides related to cyberbullying have received signi icant attention from the press. In a content analysis of 184 U.S. newspaper articles on suicides related to cyberbullying, the authors found that most articles did not adhere to guidelines on protecting against "suicidal behavioral contagion" [28].…”
Section: Cyberbullying Effectsmentioning
confidence: 99%
“…Several studies have attempted to assess adherence to suicide reporting guidelines across various countries and forms of media, including new media, with disappointing results (Abbott, Ramchand, Chamberlin, & Marcellino, 2017;Easson, Agarwal, Duda, & Bennett, 2014;John et al, 2016;Utterson, Daoud, & Dutta, 2017;Young, Subramanian, Miles, Hinnant, & Andsager, 2017). A recent study examining the fidelity of media reporting on Robin Williams' suicide found that 55% of articles surpassed the 80% threshold for "high fidelity" and 85% of articles applied at least 70% of the guidelines.…”
Section: Existing Guidelinesmentioning
confidence: 99%